Compact grid: a grid computing system using low resource compact computers. (11th September 2008) - Demiya, Takehiko; Yoshihisa, Tomoki; Kanazawa, Masanori
Recently, grid computing has attracted great attention. In grid computing, using multiple computers and executing processes in parallel, we can get great computational power. Grid computing systems usually employ regular computers such as personal computers and workstations. Although general grid computing systems do not focus on compact computers, compact computers face a problem of the lack of computational power. To solve the problem we can reap benefits of grid computing systems. In this paper, we propose a grid computing system using compact computers and develop a new prototype system. The system controls their computational powers so that processes required by the grid computing system do not interrupt commonly assigned processes for compact computers. The main target is realising grid computing, not compact computers. Also, we evaluate the prototype system and confirm the performance.